Rapid prediction of head rice yield and grain shape for genome-wide association study in indica rice. (November 2020) - Liu, Chang; Song, Jiling; Wang, Yuechan; Huang, Xirui; Zhang, Fan; Wang, Wensheng; Xu, Jianlong; Zhang, Yu; Yu, Hongxu; Pang, Yuehan; Bao, Jinsong
Abstract: Rice milling and appearance qualities are the main determinants of market price of the milled rice, so great breeding efforts have been directed to improve the milling and appearance quality. The success of breeding efforts depends on the accurate and rapid phenotyping of the quality traits in early generations. This study was conducted to first validate the effectiveness of the PaddyCheck to measure head rice yield (HRY) and paddy grain length of 40 indica rice cultivars. The results indicated that the PaddyCheck data had positively correlated with the lab methods of HRY (r = 0.81**) and grain length (r = 0.97**). An association panel including 281 indica rice accessions was phenotyped with the PaddyCheck and the data were used for genome-wide association study (GWAS) to identify quantitative trait locus (QTL) for milling and appearance quality. A total of nine QTLs were identified, among which the major genes GS3 and qSW5 were identified for grain length and width, respectively. Furthermore, a novel QTL on short arm of chromosome 6 was identified for HRY. Our study indicated that PaddyCheck measurement was accurate and effective, and could be applied in rice breeding for improvement of grain shape and milling quality. The nine QTLs identified in indica rice could be used in marker assisted selection in rice breeding programs. Graphical abstract: Image 1 Highlights: PaddyCheck was used to predict head rice yield (HRY) and grain shape. PddyCheck and lab method for HRY had highly positive correlation (r = 0.81). PddyCheck and lab method for grain length had highly positive correlation (r = 0.97). Genome-wide association study identify 9 loci for HRY and grain shape.